Penyusunan Laporan Keuangan di Kelurahan Pamulang Timur - Titah Rahmawati; Ririn Sari Dewi (Jurnal Pengabdian Kepada Masyarakat Kalam, 2023)
Kelurahan is an administrative division in Indonesia under sub-districts, which is led by a lurah. Unlike the village, the kelurahan has more limited rights to regulate its territory. Along with the pace of development that was matched by the rapid growth of the population and economy, as a buffer zone for the national capital, East Pamulang Village finally changed its status from Village to Village, namely on September 19 2005, Pamulang Timur Village, which is located at Jalan Pinang Raya Number 2 Pamulang Timur 15417. Based on Permenkeu No.22/PMK.05/2022, SAP is applied in compiling and presenting accrual-based government financial reports, namely SAP which recognizes income, expenses, assets, debt, and equity in accrual-based financial reporting, and recognizes income, spending, and financing in reporting the implementation of the budget based on the basis set out in the state revenue and expenditure budget/regional revenue and expenditure budget. In the context of accountability for the implementation of the APBN/APBD, each Reporting Entity is required to prepare and present Financial Reports and Performance Reports. Central/regional government Financial Reports consist of Budget Realization Reports, Balance Sheets, Cash Flow Reports and Notes to Financial Statements.